Nanoparticle-lipid bilayer interactions studied with lipid bilayer arrays - Lu, Bin; Smith, Tyler; Schmidt, Jacob J (Nanoscale, 2015)
The widespread environmental presence and commercial use of nanoparticles have raised significant health concerns as a result of many in vitro and in vivo assays indicating toxicity of a wide range of nanoparticle species. Many of these assays have identified the ability of nanoparticles to damage cell membranes. These interactions can be studied in detail using artificial lipid bilayers, which can provide insight into the nature of the particle-membrane interaction through variation of membrane and solution properties not possible with cell-based assays. However, the scope of these studies can be limited because of the low throughput characteristic of lipid bilayer platforms. We have recently described an easy to use, parallel lipid bilayer platform which we have used to electrically investigate the activity of 60 nm diameter amine and carboxyl modified polystyrene nanoparticles (NH2-NP and COOH-NP) with over 1000 lipid bilayers while varying lipid composition, bilayer charge, ionic strength, pH, voltage, serum, particle concentration, and particle charge. Our results confirm recent studies finding activity of NH2-NP but not COOH-NP. Detailed analysis shows that NH2-NP formed pores 0.3-2.3 nm in radius, dependent on bilayer and solution composition. These interactions appear to be electrostatic, as they are regulated by NH2-NP surface charge, solution ionic strength, and bilayer charge. The ability to rapidly measure a large number of nanoparticle and membrane parameters indicates strong potential of this bilayer array platform for additional nanoparticle bilayer studies.